2020
DOI: 10.4081/monaldi.2020.1224
|View full text |Cite
|
Sign up to set email alerts
|

Edoxaban in elderly patient with morbid obesity and atrial fibrillation: the role of plasma levels evaluation for selecting the appropriate dose

Abstract: We present the case of a 80-year-old man with atrial fibrillation, morbid obesity (weight 123 kg, height 167 cm, BMI 44.1), high clearance of creatinine and pharmacological polytherapy, in which the serial determinations of edoxaban plasma levels help us to choose the appropriate dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The reasons for the known greater thromboembolic risk in women than in men remain unclear but may include older age, under-treatment with anticoagulant therapy, and poor anticoagulation control [ 93 ]. Many studies [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] were very well designed to assess the effectiveness of NOACs versus VKAs for thromboembolic risk prevention in NVAF, but sex-associated risk during NOACs treatment is not still understood. Law et al [ 102 ] compared the effectiveness and safety outcomes of NOACs versus VKAs in 4972 men and 4834 women, showing that NOACs use was associated with a lower risk of intracranial hemorrhages (ICH) (HR: 0.16, 95% CI [0.06, 0.40]) and all-cause mortality (HR: 0.55, 95% CI [0.39, 0.77]) in women but not in men without significant differences in terms of stroke and TE incidence.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the known greater thromboembolic risk in women than in men remain unclear but may include older age, under-treatment with anticoagulant therapy, and poor anticoagulation control [ 93 ]. Many studies [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] were very well designed to assess the effectiveness of NOACs versus VKAs for thromboembolic risk prevention in NVAF, but sex-associated risk during NOACs treatment is not still understood. Law et al [ 102 ] compared the effectiveness and safety outcomes of NOACs versus VKAs in 4972 men and 4834 women, showing that NOACs use was associated with a lower risk of intracranial hemorrhages (ICH) (HR: 0.16, 95% CI [0.06, 0.40]) and all-cause mortality (HR: 0.55, 95% CI [0.39, 0.77]) in women but not in men without significant differences in terms of stroke and TE incidence.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, assessment of the anticoagulant effect of DOACs may be desirable in certain rare situations, such as extreme body weight, concomitant oncologic therapies, patients after transplantation, patients on HIV medication, etc. [ 201 , 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 Notwithstanding, real life studies have not found reduced efficacy or safety of DOACs in this population. [52][53][54][55][56] It is suggested to use VKAs instead of DOACs in extremely obese patients. If DOACs are used, monitoring of drug trough levels should be considered, switching to a VKA if drug levels fall below the expected "on therapy" range.…”
Section: Patients At the Extremes Of Body Weightmentioning
confidence: 99%